2003
DOI: 10.1046/j.1442-9071.2003.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of scleral buckling with combined scleral buckling and pars plana vitrectomy in the management of rhegmatogenous retinal detachment with unseen retinal breaks

Abstract: Conventional scleral buckling was found to be a safe and effective technique in the primary management of uncomplicated, rhegmatogenous retinal detachments with unseen retinal breaks when the media is clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
12

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 13 publications
0
34
0
12
Order By: Relevance
“…Numerous studies have been published recommending one of the two methods [1,4,13,14,20,24,26,27,29,30,32]. We could identify no consensus among several editorial comments on this issue [6, 15-18, 33, 34].…”
Section: Discussionmentioning
confidence: 93%
“…Numerous studies have been published recommending one of the two methods [1,4,13,14,20,24,26,27,29,30,32]. We could identify no consensus among several editorial comments on this issue [6, 15-18, 33, 34].…”
Section: Discussionmentioning
confidence: 93%
“…However, combining scleral buckle surgery with PPV may increase the risk of intraoperative and postoperative complications (especially choroidal haemorrhage) which occur more frequently in combined surgery [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…They found an 83% primary success rate in the PPPV group and 93% in the SBS group. Tewari et al compared SBS and PPPV in patients with undetected retinal breaks in a prospective, randomised fashion [40]. The authors found a higher reattachment rate following PPPV, but a better postoperative visual acuity following SBS; neither of the differences reached statistical significance.…”
Section: Discussionmentioning
confidence: 99%